Improving the Performance of a Microstrip Antenna by Adding a Slot into Different Patch Designs - Hakeem, M. J.; Nahas, M. M. (Engineering, Technology & Applied Science Research, 2021)
Microstrip patch antennas are attractive for communication applications due to their small size, low cost, and easy fabrication. Regardless of the diverse usage of these antennas, their bandwidth and efficiency are still limited and need to be improved. Therefore, this paper aims to enhance the bandwidth and efficiency of a microstrip antenna by inserting a slot into various patch designs. Flame Retardant (FR4) material is used in the dielectric substrate and the antenna is fed by a microstrip line. Virtually, the antenna performance is attempted to be optimized through empirical investigations of feedline lengths, slot sizes and positions, and ground plane dimensions and locations. To achieve the results, the High Frequency Structure Simulator (HFSS) is used, and the paper concludes by showing that the antenna performance is enhanced by the slot, and the return loss is significantly reduced when the ground plane is moved to the front surface of the antenna.